Continuous Electroencephalographic Monitoring in the Intensive Care Unit: A Cross-Sectional Study. (November 2020) - Koffman, Lauren; Rincon, Fred; Gomes, Joao; Singh, Sarabdeep; He, Yitian; Ritzl, Eva; Bleck, Thomas P.; Kaplan, Peter W.; Nyquist, Paul
Objective: Research on continuous electro-encephalographic monitoring (cEEG) in the intensive care unit (ICU) has previously focused on neuroscience ICUs. This study determines cEEG utilization within a sample of specialty ICUs world-wide. Methods: A cross-sectional electronic survey of attending level physicians across various intensive care settings. Twenty-five questions developed from consensus statements on the use of cEEG in the critically ill sent as an electronic survey. Results: Of all, 9344 were queried and 417 (4.5%) responses were analyzed with 309 (74%) from the United States and 74 (18%) internationally. Intensive care units were: medical (10%), surgical (6%), neurologic/neurosurgical (12%), cardiac (4%), trauma (3%), pediatrics (29%), burn (<1%), multidisciplinary (30%), and other (5%). Intensive care units were: academic (65%), community (18%), public (3%), military (1%), and other (13%). Specialized cEEG teams were available in 71% of ICUs. Rapid 24/7 access and cEEG interpretation was available in 32% of ICUs. Interpretation changed clinical management frequently (28%) and sometimes (45%). Conclusions: Despite guideline recommendations for cEEG use, there is a discordance between availability, night coverage, and immediate interpretation. Only 27% have institutional protocols for indications and duration of cEEG monitoring. Furthermore, cEEG may be underutilized in nonneurologic ICUs as well as ICUs in smaller nonacademic affiliated hospitals and those outside of the United States.